2008
DOI: 10.1080/15419060802013943
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Connexin45 with Connexin43 Decreases Gap Junction Size

Abstract: In the human heart, ventricular myocytes express connexin 43 (Cx43) and traces of Cx45. In congestive heart failure, Cx43 levels decrease, Cx45 levels increase and gap junction size decreases. To determine whether alterations of connexin coexpression ratio influence gap junction size, we engineered a rat liver epithelial cell line that endogenously expresses Cx43 to coexpress inducible levels of Cx45 under stimulation of the insect hormone, ponasterone A. In cells induced to express Cx45, gap junction sizes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…In previous studies, we found that altering connexin co-expression ratios in our cell lines directly changed the composition of gap junction channels at cell interfaces, and their cell-to-cell electrical conductance and dye permeability properties [8,17]. A noteworthy observation was that altered expression of the transfected connexins appeared to affect expression of the endogenous Cx43.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…In previous studies, we found that altering connexin co-expression ratios in our cell lines directly changed the composition of gap junction channels at cell interfaces, and their cell-to-cell electrical conductance and dye permeability properties [8,17]. A noteworthy observation was that altered expression of the transfected connexins appeared to affect expression of the endogenous Cx43.…”
Section: Introductionmentioning
confidence: 59%
“…RLE cells, engineered with the Ecdysone-Inducible Expression System (Invitrogen, CA, USA) to co-express Cx40, ind40 cells, or Cx45, ind45 cells, with endogenous Cx43, were cultured as described previously [8,17]. The mRNA expressed upon induction is a bi-cistronic mRNA, with an internal ribosome entry site between the connexin sequence and the antibiotic resistance.…”
Section: Routine Cell Culturementioning
confidence: 99%
See 3 more Smart Citations